Apical obturation quality of Epiphany/Resilon root canal filling system - Lucas da Fonseca Roberti Garcia; Lucas Zago Naves; Simonides Consani; Lourenço Correr-Sobrinho; Fernanda de Carvalho Panzeri Pires de Souza (Universidade Estadual de Campinas, 2015)
Aim: This study analyzed by scanning electronic microscopy (SEM) the quality of the apical obturation of a methacrylate based (polycaprolactone) root-canal filling system (Epiphany/Resilon) compared to that of an epoxy-resin based endodontic sealer (Sealer 26/gutta-percha). Methods: Twenty roots of human maxillary canines were debrided using ProTaper nickel-titanium rotary instruments and 2.5% NaOCl solution. The roots were divided into two groups (n=10): group I was sealed with Epiphany/Resilon and group II with Sealer 26/gutta-percha points. After set, the apical region of the roots was abraded until filling exposure and was then sectioned to obtain 2-mm-thick specimens. The specimens were analyzed by SEM and the images obtained were recorded and evaluated using an integration grid that permitted the quantification of the obturated area. Results: Statistical analysis (2-way ANOVA - Bonferroni test - p<0.05) revealed no significant difference (p>0.05) between the root canal filling systems. Conclusion: In conclusion, the two tested root canal filling systems showed similar behavior regarding to the quality of the apical obturation.